Justice climatique et mobilisations environnementales - Lydie Laigle (VertigO)
Climate justice was originally conceived as a distributive question due to differentiated responsibilities of countries in worldwide greenhouse gases emissions. Firstly, it concerns their capacities to develop mitigation policies. Secondly, it requires to back the poorest and most vulnerable countries to carry out sustainable ways of adaptation to climate change impacts. Nevertheless, this question of distributive justice is likely to evolve regarding the growing concerns of social and environmental injustices caused by climate change. In this article, we extend approaches of environmental justice to identify and characterize injustices. Theses injustices result from socio-ethnic discriminations to environmental changes, and transfers of social and ecological costs between territories and generations. They are also related to the recognition of ethical and cognitive dimensions of climate changes which are rarely integrated into democratic participation and decisions affecting natural and built environments. Finally, they reveal the influence of the democratic functioning on nature-society relations. NGOs have embraced these different topics of climate injustices and bring them into climate negotiations regarding ecological debt, human rights, indigenous sovereignty on Earth, ecological citizenship. NGOs have recently changed their forms of mobilization pursuing justice actions against states by urging them to intensify their climate policies and make them socially fairer. How do citizen and NGOs coalitions point out the weak integration of social justice issues into climate policies? To what extent do they place themselves as political interlocutors to rethink redistribution and citizen participation toward socio-ecological transition? How do these issues can be thought through democratic dialogue and turned into climate justice policies?